Industrial training report General Tun Ibrahim Library, National Defence University of Malaysia Kem Perdana Sungai Besi, Kuala Lumpur / Salzawany Abdul Karim - Abdul Karim, Salzawany (Faculty of Administrative Science and Policy Studies, 2014)
UPNM was formerly known as Akedemi Tentera Malaysia (ATMA) or the Malaysian Armed Forces Academy which was established on June 1, 1995. The institution was also branded as the sole organization responsible in upgrading the knowledge and academic status of the armed forces by offering bachelor degree courses in fields of engineering, sciences and managements while not neglecting the basic requirements of military training. The bachelor degree courses were accredited and awarded by University Teknologi Malaysia in the beginning. Lecturers - some from within the armed forces, some hired by the academy and the rest deputised by UTM where all were fully committed to changing the face of the Malaysian armed forces.